Bisphenol A Effects on Mammalian Oogenesis and Epigenetic Integrity of Oocytes: A Case Study Exploring Risks of Endocrine Disrupting Chemicals. (3rd August 2015) - Eichenlaub-Ritter, Ursula; Pacchierotti, Francesca
Abstract : Bisphenol A (BPA), originally developed as a synthetic oestrogen, is nowadays extensively used in the production of polymeric plastics. Under harsh conditions, these plastics may release BPA, which then can leach into the environment. Detectable concentrations of BPA have been measured in most analysed samples of human serum, plasma, or urine, as well as in follicular fluid, foetal serum, and amniotic fluid. Here we summarize the evidence about adverse BPA effects on the genetic and epigenetic integrity of mammalian oocytes. We conclude that increasing evidence supports the notion that low BPA concentrations adversely affect the epigenome of mammalian female germ cells, with functional consequences on gene expression, chromosome dynamics in meiosis, and oocyte development. Specific time windows, during which profound chromatin remodelling occurs and maternal imprints are established or protected, appear particularly vulnerable to epigenetic deregulation by BPA. Transgenerational effects have been also observed in the offspring of BPA-treated rodents, although the epigenetic mechanisms of inheritance still need to be clarified. The relevance of these findings for human health protection still needs to be fully assessed, but they warrant further investigation in both experimental models and humans.